Teaching: Professionalisation, Development and Leadership
XIV, 317 p.
Keywords: The world-wide reform movement has now been in process for thirty years and it is therefore perhaps an appropriate point to consider its implications for the work of teachers thus far and to ponder on the future. It would be widely agreed that the reform movement in general, and in relation to teachers’ work in particular, has brought advantages and disadvantages. It has stimulated teacher development and increased the accountability of teachers to clients – including the state as client. On the other hand, it has led to the intensification of teachers’ work and to the deprofessionalisation as well as professionalisation of teachers. Moreover, it has increased the power of managerialism over the influence of professionalism. This book addresses these issues from different perspectives and in relation to different contexts. It also considers possible solutions to two problems in particular: how to achieve accountability without intensification, and how to ensure that school management and leadership functions to support and enhance teachers as professionals.